2015
DOI: 10.3390/membranes5040844
|View full text |Cite
|
Sign up to set email alerts
|

Co-Utilization of Glucose and Xylose for Enhanced Lignocellulosic Ethanol Production with Reverse Membrane Bioreactors

Abstract: Integrated permeate channel (IPC) flat sheet membranes were examined for use as a reverse membrane bioreactor (rMBR) for lignocellulosic ethanol production. The fermenting organism, Saccharomyces cerevisiae (T0936), a genetically-modified strain with the ability to ferment xylose, was used inside the rMBR. The rMBR was evaluated for simultaneous glucose and xylose utilization as well as in situ detoxification of furfural and hydroxylmethyl furfural (HMF). The synthetic medium was investigated, after which the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
0
9
1
Order By: Relevance
“…Therefore, we considered the SSF mode with lower enzyme doses. In this process, enzymes work with fermenting microorganisms to convert the released components into bioproducts (32). Regarding the activities of enzymes correlated with carbohydrate catabolism, -mannosidase, and -fucosidase were not detected, while -andgalactosidase, -and -glucosidase, -glucuronidase activities were found in all tested strains.…”
Section: Separate Hydrolysis and Fermentation (Shf)mentioning
confidence: 99%
“…Therefore, we considered the SSF mode with lower enzyme doses. In this process, enzymes work with fermenting microorganisms to convert the released components into bioproducts (32). Regarding the activities of enzymes correlated with carbohydrate catabolism, -mannosidase, and -fucosidase were not detected, while -andgalactosidase, -and -glucosidase, -glucuronidase activities were found in all tested strains.…”
Section: Separate Hydrolysis and Fermentation (Shf)mentioning
confidence: 99%
“…In this study, fermentation was carried out in 20 l pilot plant bioreactor system integrated with firststage MF unit and second-stage NF unit. The concept of reverse MBR (rMBR) where cells are immobilized between immersed membrane layers and separated from actual substrate solution is recently introduced by Ishola et al (2015b). Cells are encapsulated between synthetic membrane layers in the form of compact multilayer membrane column or IPC flat sheet membrane (Doyen et al 2010).…”
Section: Mbrs For Fermentative Production Of Lignocellulosic Bioethanolmentioning
confidence: 99%
“…Cells are encapsulated between synthetic membrane layers in the form of compact multilayer membrane column or IPC flat sheet membrane (Doyen et al 2010). Such kind of advanced IPC rMBR configuration was used for bioethanol production from wheat straw hydrolyzate using recombinant yeast (Ishola et al 2015b). Improved simultaneous utilization of xylose and glucose with in situ detoxification of inhibitory components was facilitated by such novel configuration.…”
Section: Mbrs For Fermentative Production Of Lignocellulosic Bioethanolmentioning
confidence: 99%
“…Previous research has revealed that the increase in the concentrations of glucose decreased xylose consumption and that hexose transporter overexpression Hxt7 partially relieved the inhibitory effects of increasing glucose concentration [46]. Ishola et al [47,48] reported that glucose concentration affected xylose uptake in SSFF or in reverse membrane bioreactors. In recombinant flocculent S. cerevisiae the best ratio of glucose/xylose for the highest xylose consumption rate was 2:3 among different ratios [49].…”
Section: Effect Of Sugar Concentration On Xylose and Glucose Utilizationmentioning
confidence: 99%